Synthesis and Characterization of Biodegradable Aliphatic Polyesters - Karunanidhi, M.; Nanthini, R.; Ravi, A.; Jaisnkar, V. (Asian Journal of Chemistry, 2010)
A series of aliphatic copolyesters were prepared from, 1,4-butane diol and suberic acid, succinic acid/adipic acid through a two step process of melt polycondensation using titanium tetra isopropoxide as catalyst. The synthesized polyesters were characterized by viscosity measurements, nuclear magnetic resonance spectroscopy, gel permeation chromatography, X-ray diffraction analysis and differential scanning calorimetry. The polyesters biodegradation was investigated by enzymatic hydrolysis using the enzyme, in a buffer solution with Candida cylindracea lipase and Mucor miehei lipase. The enzymatic degradation rates for the two different enzymes were observed and compared. The changes in the structure morphology during the degradation process were studied by scanning electron microscopy. It appears that biodegradation was affected by polyester crystallinity. The lowest crystalline polyester shows highest rate of degradation in both enzymes.